Regulation of ribosomal protein synthesis in Escherichia coli B/r. - Dennis, P P (1975)
The differential synthesis rate of ribosomal protein (r-protein), alpha-r (synthesis rate of r-protein divided by synthesis rate of total protein), was measured during the cell division cycle. It was observed that alpha-r remained essentially constant and was not measurably affected by duplication of the r-protein gene cluster (i.e., str-spc region) during the process of chromosome replication. It was further observed that the rate of total protein synthesis and r-protein synthesis increased continuously and uniformly during the entire cell cycle. This gene dosage independence of the synthesis rate of r-protein was similar to that observed earlier for the synthesis of ribosomal ribonucleic acid (rRNA). These observations indicate that the synthesis rates of the protein and RNA components of the ribosome are coordinately balanced during the entire cell division cycle and are not significantly perturbed by duplication of the r-protein or rRNA genes. Furthermore, this balanced synthesis insures that neither free rRNA nor free r-protein accumulate in appreciable amounts during balanced growth.